Fluorene‐based conjugated polymer with tethered thymines: click postpolymerization synthesis and optical response to mercury(II). Issue 4 (22nd December 2012) - Lei, Yanli; Ma, Fudong; Tian, Yong; Niu, Qiaoli; Mi, Hongyu; Nurulla, Ismayil; Shi, Wei
Abstract A kind of fluorene‐based conjugated polymer with tethered thymine (T) groups {poly[(9, 9‐dioctyl)‐2, 7‐fluorene‐{9, 9‐dioctyl‐4–1, 2, 3‐triazol‐[5‐(hydroxymethyl)tetrahydrofuran‐2‐yl]‐5‐methylpyrimidine‐2, 4(1H, 3H)‐dione}‐2, 7‐fluorene]‐co‐[(9, 9‐dioctyl)‐2, 7‐fluorene‐4, 7‐bis(5‐thiophen‐2‐yl)benzo‐2, 1, 3‐thiadiazole] (P‐3)} was successfully synthesized by a Cu(I)‐catalyzed click reaction between the acetylene‐substituted polymer precursor {poly[(9, 9‐dioctyl)‐2, 7‐fluorene‐(9, 9‐dioctyl‐4‐phenylacetylene fluorene)]‐co‐[(9, 9‐dioctyl)‐2, 7‐fluorene‐4, 7‐bis(5‐thiophen‐2‐yl)benzo‐2, 1, 3‐thiadiazole]} and 3′‐azido‐3′‐deoxythymidine. The chemical structures of the intermediates and target polymer were verified by Fourier transform infrared spectroscopy and 1H‐NMR analyses. The specific binding with Hg2+ of P‐3 was corroborated by ultraviolet–visible spectroscopy and photoluminescence analyses against other metal ions. The results show that P‐3 possessed selectivity and sensitivity toward Hg2+. Around 77% of photoluminescence intensity of P‐3 was quenched when the concentration of Hg2+ reached 7.7 × 10−4M and with a detection limit in the range of about 4.8 μM. A comparison experiment suggested that a synergic effect of the tethered T and S atoms interrelated with Hg2+ existed in P‐3. Most of the fluorescence intensity of P‐3 was recovered upon the addition of iodide anions to the P‐3/Hg2+ complex; this suggested that P‐3 could be used as a potential reversible optical Hg2+ probe. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013